Provider Perspectives on Advance Care Planning Documentation in the Electronic Health Record: The Experience of Primary Care Providers and Specialists Using Advance Health-Care Directives and Physician Orders for Life-Sustaining Treatment. (December 2017) - Dillon, Ellis; Chuang, Judith; Gupta, Atul; Tapper, Sharon; Lai, Steve; Yu, Peter; Ritchie, Christine; Tai-Seale, Ming
Context: Advance care planning (ACP) is valued by patients and clinicians, yet documenting ACP in an accessible manner is problematic. Objectives: In order to understand how providers incorporate electronic health record (EHR) ACP documentation into clinical practice, we interviewed providers in primary care and specialty departments about ACP practices (n = 13) and analyzed EHR data on 358 primary care providers (PCPs) and 79 specialists at a large multispecialty group practice. Methods: Structured interviews were conducted with 13 providers with high and low rates of ACP documentation in primary care, oncology, pulmonology, and cardiology departments. The EHR problem list data on Advance Health Care Directives (AHCDs) and Physician Orders for Life-Sustaining Treatment (POLST) were used to calculate ACP documentation rates. Results: Examining seriously ill patients ≥65 years with no preexisting ACP documentation seen by providers during 2013 to 2014, 88.6% (AHCD) and 91.1% (POLST) of 79 specialists had zero ACP documentations. Of 358 PCPs, 29.1% (AHCD) and 62.3% (POLST) had zero ACP documentations. Interviewed PCPs often believed ACP documentation was beneficial and accessible, while specialists more often did not. Specialists expressed more confusion about documenting ACP, whereas PCPs reported standard clinic workflows. Problems with interoperability between outpatient and inpatient EHR systems and lack of consensus about who should document ACP were sources of variations in practices. Conclusion: Results suggest that providers desire standardized workflows for ACP discussion and documentation. New Medicare reimbursement for ACP and an increasing number of quality metrics for ACP are incentives for health-care systems to address barriers to ACP documentation.